134 Virus kinetics and biochemical derangements in children with Ebolavirus disease. (29th October 2021) - Kjaldgaard, Lindsey; Hawkes, Michael; Claude, Kasereka Masumbuko; Dixit, Devika
Abstract: Primary Subject area: Infectious Diseases Background: In the second largest outbreak of Ebolavirus disease (EVD) on record (Democratic Republic of Congo, 2018-2020), 3470 cases were confirmed, 29% of them among children under 18 years of age. Objectives: To describe virologic and biochemical characteristics of pediatric patients with EVD, and to compare these to a control group of adults with EVD. Design/Methods: Retrospective medical record review of children < 16 years old from two treatment centres in North Kivu, DRC. A control group of patients 16-44 years old was included as a reference comparator group. Patient demographics, serial measurements of viral load, serial biochemistry panel, and frequent point-of-care glucose test results were abstracted from the chart record. Funding provided by the Association for Health Innovation in Africa (AFHIA). Results: Seventy-three children and 234 adults were included, admitted from April 24 to October 14, 2019. Pediatric patients commonly had electrolyte imbalances (36% hypokalemia, 52% hyperkalemia, and 74% hyponatremia), AKI (51%), elevated liver enzymes (median peak ALT 380 IU/L and AST 570 IU/L), and rhabdomyolysis (48%). Viral load at admission (7.2 versus 6.5 log10 copies/mL, p=0.0001), peak viral load (7.5 versus 6.7 log10 copies/mL, p<0.0001), and time to clearance of viremia (16 versus 12 days p<0.0001) were significantly different in children. Duration of hospital stay (20 versus 16 days, p<0.0001) was prolonged in children, a direct consequence of slower clearance of viremia. There was no significant difference between groups in other laboratory values. Factors including ALT >525 U/L, viral load (VL) >7.6 log10 copies/mL, BUN >7.5 mmol/L, and CRP >100 mg/L were associated with mortality in children, as in adults. In a multivariable logistic regression model, ALT and VL remained statistically significant independent predictors of mortality. Conclusion: Pediatric patients with EVD, like adults, experience multi-organ involvement with life-threatening kidney and liver injury, rhabdomyolysis, and electrolyte imbalances. Pediatric patients have significantly higher viral loads throughout the course of EVD than adults.